Black History at Your Doorstep Resource Packet 1985-1986. Volume 1. - Maryland Commission on Afro-American History and Culture, Annapolis; Maryland Commission on Afro-American History and Culture, Annapolis; Maryland State Dept. of Education, Baltimore ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
This packet of resource materials was compiled to help teachers infuse the study of Afro-American history and culture into the curriculum throughout the school year. The packet contains both informational materials and sample activities. In order to assist teachers in studying the Afro-American experience in their own communities, special emphasis was placed on three subject areas; (1) the Afro-American family; (2) oral history techniques; and (3) the Afro-American experience in Maryland. Special activities follow each of these sections. Reproducible classroom activities for elementary and secondary students are included covering a wide variety of topics relating to Afro-Americans. Other items in the packet include: (1) a listing of libraries, archives, and museums in Maryland for studying Afro-American history; (2) an 81-item annotated bibliography of books and audio/visual aids; and (3) a speakers list of resource people having expertise in various topics related to Afro-Americans. (JB)
ERIC Note: Portions contain smudged type. Best copy available.
Teachers.
Students.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Achievement; Black Culture; Black History; Black Literature; Black Studies; Curriculum Enrichment; Elementary Secondary Education; Genealogy; Racial Attitudes; Racial Bias; Racial Relations; Resource Materials; Social Attitudes; Maryland; Guides, Classroom -- Learner; Guides, Classroom -- Teacher; Reference Materials, General